Reformulation of Business Strategy PT XYZ - Saparuddin Mukhtar; Mohammad Rizan; Resti Annisa; Rifelly Dewi Astuti; Basri Bado (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
Currently, PT. XYZ requires the restructuring of its business strategy to restore and restore PT XYZ 's finances as well as to build a viable and profitable housing. In the reformulation of the business strategy of PT XYZ, the researcher will use SWOT analysis as the basis of the analysis, and Grand Strategy matrix to analyze company position in the industry. The results indicate that the position of PT XYZ is in the quadrant 1 is Strength—Opportunity which means the position of a perfect company strategy and competes vigorously. The alternative strategy formed refers to the related Diversification strategy and Horizontal Integration, the suggested strategy is (1) to build a Highland geopark tourism park; (2) redeveloping the extreme sports arena; (3) establish cooperative relationships with government or private companies concerned; (4) to provide land or field intended for residents of housing around PT XYZ area, also a form of CSR; (5) evaluate and improve HR performance by conducting performance appraisal through key performance indicator and balanced scorecard.